2014
DOI: 10.1091/mbc.e13-09-0523
|View full text |Cite
|
Sign up to set email alerts
|

NAADP and the two-pore channel protein 1 participate in the acrosome reaction in mammalian spermatozoa

Abstract: A TPCN1 gene–deficient mouse strain is used to show that two convergent working NAADP-dependent pathways with nonoverlapping activation and self-inactivation profiles for distinct NAADP concentrations drive acrosomal exocytosis, by which TPC1 is central for the pathway activated by low-micromolar NAADP concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 139 publications
(191 reference statements)
2
65
0
Order By: Relevance
“…However given the capacity of mouse embryos to compensate for loss of expression of important Ca 2+ signalling proteins by 'remodelling' other signalling pathways (Berridge et al, 2003), this does not exclude the possibility of important roles for TPCs during mammalian reproduction and embryogenesis. Indeed, a recent study that investigated the role of NAADP and TPCs in sperm biology found that NAADP could activate the acrosome reaction, whereas this response was blocked by treatment with Ned-19, as well as being absent in TPC1 knockout mice (Arndt et al, 2014). The study also found that NAADP binding sites and TPC1 showed co-localisation in the acrosomal region, providing further support for the idea that TPCs are NAADP-regulated Ca 2+ channels.…”
Section: Role Of Naadp and Tpcs During Fertilization And Embryogenesismentioning
confidence: 59%
See 1 more Smart Citation
“…However given the capacity of mouse embryos to compensate for loss of expression of important Ca 2+ signalling proteins by 'remodelling' other signalling pathways (Berridge et al, 2003), this does not exclude the possibility of important roles for TPCs during mammalian reproduction and embryogenesis. Indeed, a recent study that investigated the role of NAADP and TPCs in sperm biology found that NAADP could activate the acrosome reaction, whereas this response was blocked by treatment with Ned-19, as well as being absent in TPC1 knockout mice (Arndt et al, 2014). The study also found that NAADP binding sites and TPC1 showed co-localisation in the acrosomal region, providing further support for the idea that TPCs are NAADP-regulated Ca 2+ channels.…”
Section: Role Of Naadp and Tpcs During Fertilization And Embryogenesismentioning
confidence: 59%
“…The study also found that NAADP binding sites and TPC1 showed co-localisation in the acrosomal region, providing further support for the idea that TPCs are NAADP-regulated Ca 2+ channels. Interestingly, two narrow bellshaped dose-response curves were identified with maxima in either the nanomolar or low micromolar NAADP concentration range, with TPC1 being found to be responsible for activating the low affinity pathway by means of analysis of the TPC1 knockout (Arndt et al, 2014). This raises the question of whether the high affinity pathway involves TPC2, an issue that remains to be explored.…”
Section: Role Of Naadp and Tpcs During Fertilization And Embryogenesismentioning
confidence: 99%
“…Being a Na ϩ /H ϩ -exchanger, its loss may change both vesicular pH and Na ϩ concentration. These changes can secondarily affect other luminal ion concentrations like that of Ca 2ϩ , the release of which may be needed for vesicle fusion and trafficking (53)(54)(55). Although not quite reaching the pH of lysosomes, the luminal pH of acrosomes (pH ϳ5.3) (56, 57) is more acidic than that of the Golgi (estimated pH ϳ5.9 -6.3, depending on cell type) (58 -60).…”
Section: Loss Of Nhe8 Disrupts Acrosome Formation In Micementioning
confidence: 99%
“…The acrosome is characterized by the unique properties of sperm cells, and acrosomal enzyme contains various hydrolytic enzymes that allow sperm to break through the external barrier to the oocyte [1][2][3][4]. Sperm can release a variety of enzymes after the acrosome reaction to stimulate sperm cells to combine with egg cells.…”
Section: Introductionmentioning
confidence: 99%